2010
DOI: 10.1104/pp.110.157537
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ZmLEC1 and ZmWRI1 Increases Seed Oil Production in Maize    

Abstract: Increasing seed oil production is a major goal for global agriculture to meet the strong demand for oil consumption by humans and for biodiesel production. Previous studies to increase oil synthesis in plants have focused mainly on manipulation of oil pathway genes. As an alternative to single-enzyme approaches, transcription factors provide an attractive solution for altering complex traits, with the caveat that transcription factors may face the challenge of undesirable pleiotropic effects. Here, we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
305
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(328 citation statements)
references
References 27 publications
(41 reference statements)
12
305
0
Order By: Relevance
“…A recent study showed seed-specific expression ZmWRI1, a WRI1-like gene of maize (Zea mays), enhanced oil accumulation in transgenic maize without detectable abnormalities. However, expression of ZmLEC1 under similar conditions severely affected growth and development of the resulting transgenic maize plants (Shen et al, 2010). Similar results were obtained by constitutive overexpression of the ZmWRI1 gene in the transgenic maize plants (Pouvreau et al, 2011).…”
supporting
confidence: 73%
See 2 more Smart Citations
“…A recent study showed seed-specific expression ZmWRI1, a WRI1-like gene of maize (Zea mays), enhanced oil accumulation in transgenic maize without detectable abnormalities. However, expression of ZmLEC1 under similar conditions severely affected growth and development of the resulting transgenic maize plants (Shen et al, 2010). Similar results were obtained by constitutive overexpression of the ZmWRI1 gene in the transgenic maize plants (Pouvreau et al, 2011).…”
supporting
confidence: 73%
“…A detailed analysis of major agronomic traits of the field-grown T3 homozygous plants revealed that the transgenic plants were phenotypically similar to Westar plants in most categories, including 1000-seed weight and the seed yield (Supplemental Table S1). Because AtLEC1 acts upstream of ABSCISIC ACID INSENSITIVE3, a key regulator of seed maturation and seed germination (Koornneef et al, 1984;Kagaya et al, 2005), and also because seed-specific expression of ZmLEC1 causes reduced seed germination (Shen et al, 2010), we compared the germination rate of the transgenic seeds with Westar seeds. No difference of the germination rate was found between Westar and the transgenic seeds (Supplemental Fig.…”
Section: Generation and Characterization Of Transgenic Rapeseed Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with other analysis showing that ectopic expression of LEC1, FUSCA3 (FUS3), and LEC2 genes induces the accumulation of lipid and protein reserves characteristic of developing seeds in cells of vegetative and reproductive tissues (Lotan et al, 1998;Stone et al, 2001Stone et al, , 2008Santos-Mendoza et al, 2005). Moreover, seed-specific overexpression of maize (Zea mays) LEC1 (ZmLEC1) resulted in an average 35% increase in seed oil but reduced germination and vegetative growth in the field (Shen et al, 2010) In Arabidopsis, the seed maturation program is controlled by a network of transcription factors that includes the B3 domain transcription factors (ABA-INSENSITIVE3 [ABI3], FUS3, and LEC2; Giraudat et al, 1992;Luerssen et al, 1998;Stone et al, 2001) and two LEC1-type HAP3 family CCAAT-binding factors, LEC1 and L1L (Lotan et al, 1998;Kwong et al, 2003). Given that these transcription factors have strong positive roles in promoting seed-specific programs, mechanisms have evolved to ensure that their expression is suppressed during vegetative growth.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, WRI1 can be considered as a "master regulator" that controls transcription of almost all key enzymes that convert sucrose to FA. The importance of WRI1 was confirmed when seed oil was increased by 30% in field trials of maize that overexpress WRI1 (12), an increase that would be valued at $2 billion if extended to all maize production in the United States. In addition to controlling oil production in seeds, recent evidence indicates that WRI1 is likely a major factor responsible for the extremely high oil content (up to 90% of tissue weight) produced by oil palm mesocarp.…”
Section: Regulation Of Fatty Acid Supply By Plastidsmentioning
confidence: 85%